Zákoník práce : komentář - Vysokajová, Margerita, 1954-; Kahle, Bohuslav, 1941-; Randlová, Nataša, 1967-; Hůrka, Petr, 1974-; Doležílek, Jiří, 1963- (Komentáře (Wolters Kluwer ČR). Kodex, 2015)
Komentované znění zákoníku práce na základě právního stavu k 1. 10. 2015.